Feasibility Analysis Of Mr. Salani’s Palm Sugar Business In Pelalo Village Sindang Kelingi Subdistrict Rejang Lebong Regency - Sefty Aulia; Sulisti Afriani; Herlin Herlin (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to determine the total costs, revenue, income, and assess the feasibility of Mr. Salani’s palm sugar business. The study is located in Pelalo Village, Sindang Kelingi District, Rejang Lebong Regency. The analysis methods used to assess the business feasibility include Total Cost Analysis, Revenue, Income, R/C Ratio, B/C Ratio, Price BEP, and Production BEP. The results show that the total cost incurred by Mr. Salani in producing palm sugar in August 2024 was Rp 1,690,275.00. The revenue from palm sugar production was Rp 3,978,000.00, with a net income of Rp 2,287,725.00. The R/C Ratio is 2.35 > 1, B/C Ratio is 1.35 > 1, Price BEP is Rp 7,648.00, and Production BEP is 4.2 kg. Therefore, it can be concluded that Mr. Salani’s palm sugar business in Pelalo Village, Sindang Kelingi District, Rejang Lebong Regency is feasible to operate.